2018
DOI: 10.1021/acs.jpcc.8b07142
|View full text |Cite
|
Sign up to set email alerts
|

Growth of In-Plane Ge1–xSnx Nanowires with 22 at. % Sn Using a Solid–Liquid–Solid Mechanism

Abstract: Germanium−tin alloys have gained strong attention because of their optical and electrical properties and their compatibility with silicon-based technologies. By increasing the Sn content in the alloy, the charge carrier mobility can be improved, and the energy band gap can be transformed from indirect to direct. However, the fabrication of GeSn is a huge challenge as the equilibrium solubility of Sn in Ge is limited to <1 at. %. The aim of this study is the fabrication of in-plane GeSn nanowires catalyzed by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…For practical applications in optoelectronic and electric devices, the thermal stability of Ge 1−x Sn x material is a crucial property which has been widely studied and reported [17,23,24,[41][42][43][44][45]. Zaumseil et al showed that the tin segregation temperature of Ge 1−x Sn x alloys increases with decreasing Sn content, and that Ge 0.91 Sn 0.09 was stable at temperatures up to 400°C [17].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For practical applications in optoelectronic and electric devices, the thermal stability of Ge 1−x Sn x material is a crucial property which has been widely studied and reported [17,23,24,[41][42][43][44][45]. Zaumseil et al showed that the tin segregation temperature of Ge 1−x Sn x alloys increases with decreasing Sn content, and that Ge 0.91 Sn 0.09 was stable at temperatures up to 400°C [17].…”
Section: Resultsmentioning
confidence: 99%
“…Ge 1−x Sn x alloys are commonly fabricated using ion implantation, laser melting [4,5,19], molecular beam epitaxy (MBE) [7], and chemical-vapor deposition(CVD) approaches [6,[20][21][22]. Apart from these thin film based preparations, there are limited reports of the synthesis of anisotropic Ge 1−x Sn x nanostructures by top-down and bottom-up approaches [12,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we know, incorporating tin ( α ‐Sn) into Ge material has been proved to be an effective method to engineer the bandgap of the indirect L ‐valley and direct Γ‐valley, and similar to direct‐band‐gap III–V or II–VI group semiconductor compounds, GeSn alloys can be integrated into photonic circuits and used as light emitter, which consists of only group IV elements. Recently, apart from the bulk GeSn alloys, many experimental researchers also focused on low‐dimensional GeSn‐related systems, such as GeSn quantum dots (QDs), nanowires (NWs) or core‐shell nanowires, and quantum wells (QWs) . In these experiments, GeSn or straind GeSn related low‐dimensional structures with Sn fraction larger than 10% have been realized, and especially GeSn NWs with very high Sn content, namely 22% and 30%, have also been reported.…”
mentioning
confidence: 99%